Physics of Atomic Nuclei - Dalkarov, Oleg D.; SpringerLink (Online service) (Moscow : Pleiades Publishing : Imprint: Pleiades Publishing.)
Physics of Atomic Nuclei (Yadernaya fizika) was founded in 1965 as the leading Russian journal on elementary particles and nuclei. The topics covered are the experimental and theoretical studies of nuclear physics: nuclear structure, spectra, and properties; radiation, fission, and nuclear reactions induced by photons, leptons, hadrons, and nuclei; fundamental interactions and symmetries; hadrons (with light, strange, charm, and bottom quarks); particle collisions at high and superhigh energies; gauge and unified quantum field theories, quark models, supersymmetry and supergravity, astrophysics and cosmology. The journal is intended for researchers, nuclear engineers, and universities.
Keywords: Nuclear physics; Particle and Nuclear Physics